Interweaving the Americas: a transnational metamorphosis autoethnography to transgress Ecuadorian education for Buen Vivir - Minchala Buri, Olga Elizabeth (Kansas State University, 2022)
The paradigm of Buen Vivir (Good Living) in education turns on the educational purpose regarding the transformation of the world. This autoethnography, which draws from transnationalism theory (Vertovec, 2009) and transnational academic mobility (Kim, 2010), explores how my critical self-examination of transformation shaped my lived experiences within transnational spaces to advance the conversation on postcolonial entanglements in education from the standpoint of a transnational migrant scholar and educator. Throughout three academic mobility journeys between Western and Latin American society, I explore privileges and disempowerment afforded me by my education, laden with postcolonial influences. To think about a different kind of education presumes recognizing and learning from my transnational lived experiences that evolved through the seven stages of Conocimiento (Anzaldúa, 2015). These lived experiences flourished my transnational identity capital (Kim, 2010) and activated my spirit for advocating for pedagogies for social transformation, relevancy, autonomy, resistance, liberation, and dialogue. This inquiry uses writing as a method, process, and product (Richardson & St. Pierre, 2005), strategies for self-narratives data collection (Chang, 2016), narrative portraits analytical strategy (Rodríguez-Dorans & Jacobs, 2020), arts-based (Barone & Eisner, 2012), and poetic (Cahnmann-Taylor, 2003) approaches for representation. By creating a self-portrait artwork and the composition of a poem, I aim to inform, inspire, and reveal my self-exposure in my findings, which authenticates my critical/decolonial thinking by merging artistic practices with autoethnographic research. I reflectively, critically, and evocatively explore and disclose vulnerabilities, positionality, and perspectives as disruptive experiences of my progressive metamorphic process that initiates from my self-identification as an Azogueña caterpillar to transmute myself to a transnational purple butterfly.
Keywords: Autoethnography; Transnationalism; Americas